Talabalarda ахbоrоt mаdаniуаtini rivоjlаntirishning pedagogik mexanizimlari (SCIENCE and SOCIETY, 2025)
This article describes the content and main goal of information culture in students as a system of competencies for working with information and communication technologies, which are necessary for students to effective- ly implement professional activities, the main purpose of which is to create conditions for the positive development of students’ personalities in an information society. published. Together with Suning, the methodology for organizing circles for schoolchildren, taking into account their interests, is explained. A computer and information technology club is an organizationally formalized (formed) association of students interested in computer technologies and information technolo- gies operating on the basis of higher education, which mainly carries out information activities with access to the Internet.